An Analysis of the Behaviour of Prime Lending Rates in Sri Lanka - Perera, W. S. Navin (Asian Journal of Economics and Empirical Research, 2018)
The prime lending rate is the rate at which commercial banks loan funds to their most creditworthy customers, and hence, is usually lower than other market lending rates; reason why it is considered a “base or reference rate”. In Sri Lanka, the Central Bank of Sri Lanka (CBSL) has been compiling the Average Weighted Prime Lending Rate (AWPR) since January 1986. This paper examines the determinants of prime lending rates in Sri Lanka using weekly data from January 2004 to June 2013, while attempting to capture any asymmetries in prime rate changes to monetary policy decisions. Empirical evidence suggests that the prime rate is highly persistent, while the call money rate also remains a key determinant. However, domestic liquidity was statistically insignificant and even if it was, it has only a marginal impact in determining the prime lending rate. Furthermore, there is also evidence of asymmetric adjustment in AWPR.